Pharmacokinetics and metabolism of [14C]-tozadenant (SYN-115), a novel A2a receptor antagonist ligand, in healthy volunteers. (3rd August 2017) - Mancel, Valérie; Mathy, François-Xavier; Boulanger, Pierre; English, Stephen; Croft, Marie; Kenney, Christopher; Knott, Tarra; Stockis, Armel; Bani, Massimo
Abstract: 1. This phase-I study (NCT02240290) was designed to investigate the human absorption, disposition and mass balance of 14 C-tozadenant, a novel A2a receptor antagonist in clinical development for Parkinson s disease. 2. Six healthy male subjects received a single oral dose of tozadenant (240 mg containing 81.47 KBq of [ 14 C]-tozadenant). Blood, urine and feces were collected over 14 days. Radioactivity was determined by liquid scintillation counting or accelerator mass spectrometry (AMS). Tozadenant and metabolites were characterized using HPLC-MS/MS and HPLC-AMS with fraction collection. 3. At 4 h, the C max of tozadenant was 1.74 μg/mL and AUC(0– t ) 35.0 h μg/mL, t 1/2 15 h, Vz/F 1.82 L/kg and CL/F 1.40 mL/min/kg. For total [ 14 C] radioactivity, the C max was 2.29 μg eq/mL at 5 h post-dose and AUC(0– t ) 43.9 h μg eq/mL. Unchanged tozadenant amounted to 93% of the radiocarbon AUC(0–48h) . At 312 h post-dose, cumulative urinary and fecal excretion of radiocarbon reached 30.5% and 55.1% of the dose, respectively. Unchanged tozadenant reached 11% in urine and 12% of the dose in feces. Tozadenant was excreted as metabolites, including di-and mono-hydroxylated metabolites, N/O dealkylated metabolites, hydrated metabolites. 4. The only identified species circulating in plasma was unchanged tozadenant. Tozadenant was primarily excreted in urine and feces in the form of metabolites.